Sistem Informasi Arsip Digital Puskesmas Cogreg Dengan Menggunakan Metode RAD - Ningrum, Apita; Persada, Ghema Nusa (Journal of Information Systems and Business Technology, 2026)
This research addresses the challenges faced by Puskesmas Cogreg in managing physical archives, including difficulty in accessing and searching for documents, risk of data loss, and inefficient archival processes. The aim of this study is to develop a digital archive system that will streamline the management of personnel data, incoming and outgoing letters, and other documents at Puskesmas Cogreg. The system uses the RAD (Rapid Application Development) methodology to create a web-based application that improves efficiency, enhances data security, and reduces the risk of document damage. The study utilizes methods such as literature review, observation, interviews, and documentation for data collection. The system was designed iteratively, with a focus on user feedback to ensure it meets the needs of Puskesmas Cogreg staff. The results show that the digital archive system successfully reduces the time and effort needed to manage documents, enhances data security, and improves operational efficiency. The conclusion highlights that the digital archive system is a practical solution to the archival challenges at Puskesmas Cogreg, and it is recommended for implementation to improve administrative processes.